2005
DOI: 10.1191/0969733005ne816oa
|View full text |Cite
|
Sign up to set email alerts
|

Two Women with Multiple Sclerosis and Their Caregivers: conflicting normative expectations

Abstract: It is not uncommon that nurses are unable to meet the normative expectations of chronically ill patients. The purpose of this article is to describe and illustrate Walker's expressive-collaborative view of morality to interpret the normative expectations of two women with multiple sclerosis. Both women present themselves as autonomous persons who make their own choices, but who also have to rely on others for many aspects of their lives, for example, to find a new balance between work and social contacts or to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Following Meichenbaum's & Turk's [18] example, we use the term 'adherence' or dialogic compliance: an active and voluntary involvement of the patient based on collaboration, in which the patient and the professional work jointly towards a desired outcome (adherence). In the context of this study, this means that decisions are made jointly and responsibilities are allotted through processes of shared decision making at various times during admission, such as the intake interview as conducted by nurses [19,20] . Linked to this process of shared decision making, patients articulate specific normative expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Following Meichenbaum's & Turk's [18] example, we use the term 'adherence' or dialogic compliance: an active and voluntary involvement of the patient based on collaboration, in which the patient and the professional work jointly towards a desired outcome (adherence). In the context of this study, this means that decisions are made jointly and responsibilities are allotted through processes of shared decision making at various times during admission, such as the intake interview as conducted by nurses [19,20] . Linked to this process of shared decision making, patients articulate specific normative expectations.…”
Section: Discussionmentioning
confidence: 99%
“…The fatigue intrudes in their personal lives and social contacts. It can be a struggle to find out which values are most important in a situation and sometimes a new balance in life is found by giving up one's working career, a process that is well known from the literature on chronic diseases and disabilities [24,25]. Rehabilitation and policy should therefore not be solely focused on returning to work, but on supporting people to regain a valuable role and on taking part, giving something and being someone in a specific context.…”
Section: Meaningful Participationmentioning
confidence: 97%
“…Koch and Kelly (1999b) stated that, when meeting health care personnel, women with MS often experienced being met with deficient knowledge of their individual situation and needs. Women with MS did not experience recognition of their vulnerability and lacked space for feelings of grief and powerlessness when meeting health care personnel (Abma, Oeseburg, Widdershoven, Goldsteen, & Verkerk, 2005). Courts, Buchanan, and Werstlein (2004) demonstrated that people with MS describe living with the illness before the diagnosis as a time of suffering because of the feeling of not being reliable in the view of others.…”
mentioning
confidence: 98%